Coyote Steals Fire - Northwestern Band of the Shoshone Nation (Utah State University, University Libraries, 2005)
""Coyote was tired of being cold,"" says this traditional Shoshone tale about the arrival of fire in the northern Wasatch region.Members of the Northwestern Band of the Shoshone Nation developed the concept for this retelling in collaboration with book arts teacher Tamara Zollinger. Together, they wrote and illustrated the book.Bright watercolor-and-salt techniques provide a winning background to the hand-cut silhouettes of the characters. The lively, humorous story about Coyote and his friends is complemented perfectly by later pages written by Northwestern Shoshone elders on the historical background and cultural heritage of the Shoshone nation.An audio CD with the voice of Helen Timbimboo telling the story in Shoshone and singing two traditional songs makes this book not only good entertainment but an important historical document, too.Sure to delight readers of all ages, Coyote Steals Fire will be a valuable addition to the family bookshelf, elementary classroom, and the school or public library.